Four distinct structural domains in Clostridium difficile toxin B visualized using SAXS. - Albesa-Jové, D; Bertrand, T; Carpenter, E; Swain, G; Lim, J; Zhang, J; Haire, L; Vasisht, N; Braun, V; Lange, A; von Eichel-Streiber, C; Svergun, D; et al. (2010)
Clostridium difficile is a nosocomial bacterial pathogen causing antibiotic-associated diarrhea and fatal pseudomembranous colitis. Key virulence factors are toxin A and toxin B (TcdB), two highly related toxins that are members of the large clostridial toxin family. These large multifunctional proteins disrupt cell function using a glucosyltransferase domain that is translocated into the cytosol after vesicular internalization of intact holotoxin. Although substantial information about the biochemical mechanisms of intoxication exists, research has been hampered by limited structural information, particularly of intact holotoxin. Here, we used small-angle X-ray scattering (SAXS) methods to obtain an ab initio low-resolution structure of native TcdB, which demonstrated that this molecule is monomeric in solution and possesses a highly asymmetric shape with a maximum dimension of approximately 275 A. Combining this SAXS information with crystallographic or modeled structures of individual functional domains of TcdB reveals for the first time that the three-dimensional structure of TcdB is organized into four distinct structural domains. Structures of the N-terminal glucosyltransferase, the cysteine protease, and the C-terminal repeat region can be aligned within three domains of the SAXS envelope. A fourth domain, predicted to be involved in the translocation of the glucosyltransferase, appears as a large solvent-exposed protrusion. Knowledge of the shapes and relative orientations of toxin domains provides new insight into defining functional domain boundaries and provides a framework for understanding how potential intra-domain interactions enable conformational changes to propagate between domains to facilitate intoxication processes.